Copper(I) Complexes Bases on a New Indazol-4,7-Dione Ligand - Guerrero-Nunez, J; Guerrero-Nunez, J; Lemus-Chavez, L; Lemus-Chavez, L (Elsevier Ltd, 2013)
Two new isomeric ligands, 1-(1-((2,6-diisopropylphenyl)imino)ethyl)-1H- benzo[f]indazole-4,9-dione (La) and 2-(1-((2,6-diisopropylphenyl) imino)ethyl)-2H-benzo[f]indazole-4,9-dione (Lb), were synthesized and fully characterized as well the derivative copper complexes; [CuI(Lb)2] (ClO 4) (1) homoleptic and [CuI(Lb(PPh3)2] (ClO 4) (2) heteroleptic copper(I) complexes. The X-ray diffraction shows an irregular tetrahedral coordination around of metal in both monometallic complexes with little differences in Cu-N distances and N-Cu-N bite angles than involved the indazole ligand between two complexes. The proton spectra show a different variation in chemical shift relative to free ligand, which was discussed by steric and magnetic current effects of another coordinated ligand. The differences in the energy of metal-to ligand-charge-transfer (MLCT) and in redox potentials to CuII/CuI process in both complexes show the notorious influence of the phosphine which by back-donating effect, modified the energy of HOMO orbital centered in Cu atom. The coordinative and redox stability in solution was established for several days in non-coordinating solvent. However in acetonitrile the ligand substitution is very fast. © 2013 Elsevier Ltd. All rights reserved.